A novel low-resistance duct tee emulating a river course. (15th October 2018) - Gao, Ran; Zhang, Hengchun; Li, Angui; Liu, Kaikai; Yu, Shengrui; Deng, Baoshun
Abstract: Duct fittings are integral parts of a duct system and play important roles in fluid transportation. Resistance within the component directly affects the energy consumed by fans and pumps. This paper proposes a novel low-resistance duct tee by emulating a natural river configuration and theoretically explains the mechanism of resistance reduction in ducts based on variations in dissipation and displacement terms in the NS equation. The novel tee can reduce resistance in straight ducts with any flow ratios and aspect ratios, with a resistance reduction rate from 20.45% to 248.21%. The novel tee can also reduce resistance in branch ducts only when the flows in straight ducts are larger than in branch ducts, and the resistance reduction rate is between 0 and 817.88% (The resistance reduction rate is the degree of resistance reduction achieved by the novel duct tee). The resistance reduction rate can be improved to above 100% when the increased amplitude of momentum dissipation is below the increased amplitude of momentum convection. The turbulence model was selected based on the full-scale experiment. The resistance reduction effect of the novel tee is validated via a full-scale experiment at the end of this paper. Abstract : A novel concave-shape tee was developed based on the emulation of a river course. The duct resistance reduction rates were between 20.45% to 817.88%. The competition between the convective and dissipation terms was analysed.